Case Report: Trastuzumab deruxtecan in human epidermal growth factor receptor 2-mutated lung cancer with continuous renal replacement therapy - Wu, Sumin; Ke, Chengming; Wei, Min (Frontiers in Oncology, 2026)
BackgroundHuman epidermal growth factor receptor 2 (HER2)-mutated lung cancer is a rare and aggressive subtype of non-small cell lung cancer (NSCLC), characterized by poor prognosis and limited response to conventional therapies. Trastuzumab deruxtecan (T-DXd), a HER2-targeting antibody-drug conjugate (ADC), has shown promising results in HER2-mutated cancers. However, its safety and efficacy in patients with renal dysfunction requiring continuous renal replacement therapy (CRRT) remain unclear.Case summaryA 69-year-old female with advanced HER2-mutant NSCLC developed acute kidney injury (AKI) requiring intermittent CRRT after failing standard chemotherapy. With strong patient commitment, T-DXd was initiated following multidisciplinary discussion. Although severe myelosuppression occurred following targeted therapy, it resolved with appropriate supportive care. Notably, no significant toxicities such as interstitial lung disease, hepatotoxicity, or further nephrotoxicity were observed. After three cycles of T-DXd, symptomatic improvement was achieved, including resolution of abdominal distension, significant reduction of ascites, and disappearance of hematuria. Follow-up imaging studies confirmed stable disease. Unfortunately, the patient succumbed to aspiration, which precluded administration of further T-DXd cycles.ConclusionT-DXd treatment in this CRRT-dependent patient with HER2-mutant lung cancer achieved disease control with manageable toxicity. While demonstrating potential clinical utility, the short survival period warrants cautious interpretation. Further validation is needed to establish its role in this population.